Kinerja Dinas Koperasi, Usaha Kecil Menengah Perdagangan dan Perindustrian dalam Upaya Menangani Kemiskinan Melalui Program “Sukabumi Kece” di Kota Sukabumi - Irpandea Putra Sutriyana; Dine Meigawati; Yana Fajar Basori (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This research is entitled "Performance of the Cooperative Service, Small and Medium Enterprises, Trade and Industry in an effort to overcome poverty through the small Sukabumi program in Sukabumi City". This study aims to provide an overview of how the performance of the Sukabumi City Diskopdagri in dealing with poverty in Sukabumi City. This research is motivated by the problem of not yet optimal implementation of the Sukabumi Kece program carried out by Diskopdagrin against poverty in Sukabumi City. In addition, the training and assistance program provided by the Sukabumi City Diskopdagrin to the community did not fully run optimally due to the COVID-19 pandemic which resulted in this program being carried out first before its implementation. The method used in this research is descriptive qualitative research method. The data collection techniques were carried out through observation, interviews and documentation. The results of this study indicate that the implementation of the Sukabumi Kece program is still not optimal in dealing with poverty in Sukabumi City.